THE RELATION BETWEEN HOME INDUSTRY ACTIVITY AND EMPLOYMENT ON ECONOMIC GROWTH TO CREATE A SUSTAINABLE ECONOMY COMMUNITY IN KOTA PARI VILLAGE - Fadlan, Ahmad; Pane, Sanusi Ghazali; Rangkuty, Ika Herawaty (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Ideally, the growing number of industries will generate employment possibilities for the local population. The fact that many residents in Kota Pari, Deli Serdang Regency, do not have good jobs, however, is still a major problem. Even if Kota Pari is home to many home industries, they should nonetheless offer employment opportunities and decent pay to those without the funds to launch their own companies. Meanwhile, via effective administration of Regional-Owned Enterprises (BUMD) targeted at boosting the economy, the potential of villages and community resources can be maximized. To learn more about the job absorption from the current home industries in Kota Pari, Deli Serdang Regency, this research is essential. Economic growth is greatly impacted by the creation of home businesses, which should also benefit many communities by creating jobs and providing other social advantages. The large number of Kota Pari hamlets with home-based businesses ought to be used as a model for other villages that the Village Government can use to boost and expand Village-Owned Enterprises (BUMDES). According to the study's findings, Kota Pari village's economic growth was positively and significantly impacted by variables X1 and X2 (employment and home industry activity) at the same time. It is expressed favorably because economic growth will rise in tandem with improved domestic industrial activity and employment. Conversely, economic growth will also slow down if current domestic industrial activity and employment decline